Neoliberal governance and international medical travel in Malaysia - Ormond, Meghann (London : Routledge, 2013)
'International medical travel (IMT), people crossing national borders in the pursuit of healthcare, has become a growing phenomenon. With many of the countries currently being promoted as IMT destinations holding developing status, IMT poses a significant challenge to popular assumptions about who provides and receives care since it inverses and diversifies presumed directionalities of care.This book analyses the development of international medical travel in Malaysia. It challenges embedded assumptions about the sources, directions and political value of care. The author situates the Malaysian case study material at the fruitful cross-section of a range of literatures such as international medical travel (IMT); the role of cross-border mobility in the construction of identity; care and hospitality; therapeutic landscapes; place-branding and medical diplomacy. The book thus contributes to wider debates that have emerged around the changing character of global health governance'--Provided by publisher.
Includes bibliographical references (p. 132-157) and index.
Keywords: Medical Tourism -- Malaysia; Politics -- Malaysia